Two new species of Gabophlias (Crustacea, Amphipoda, Phliantidae) from Australia - Coleman, Ch. Oliver; Lowry, James K. (Zootaxa, 2012)
Two new species of the genus Gabophlias are described and compared with the only previously known species from thisgenus, Gabophlias olono J.L. Barnard, 1972. Different from this species, the dorsum of Gabophlias gabiae sp. nov. doesnot have a carina. Gabophlias kerstinae sp. nov. has a dorsal carina, but it is very shallow on pereonite 1, whereas G. olonohas a large mid-dorsal process on pereonite 1. All three species can also be distinguished from each other by characteristics on antenna 1.